Micropenis - Jeremy Wiygul; Lane S. Palmer (The Scientific World Journal)
Micropenis is part of a larger group of conditions broadly known as inconspicuous penis; however, it is fundamentally different from the other diagnoses in this group, such as webbed penis and buried penis, in that the underlying problem is the size of the penis itself, not with the surrounding and overlying skin. This condition is usually the result of a defect in the hypothalamic-pituitary-gonadal axis, although iatrogenic causes are identified infrequently. Management revolves around testosterone (direct administration or encouraging the patient's body to make its own), and long-term results with respect to increase in penile length are promising. Reconstructive surgery is based on the use of a vascular pedicle free flap and is reserved for patients who fail to respond to hormonal treatment. Although substantial long-term data are lacking, adult patients with micropenis appear to report dissatisfaction with penile appearance, but the majority appear to have adequate sexual function.